A Numerical and Experimental Study to Compare Different IAQ-Based Smart Ventilation Techniques - Marcos Batistella Lopes; Najwa Kanama; Baptiste Poirier; Gaelle Guyot; Michel Ondarts; Evelyne Gonze; Nathan Mendes (Buildings)
Maintaining indoor environmental quality in residential buildings is essential for occupants’ comfort, productivity, and health, with effective mechanical ventilation playing a key role in removing or diluting indoor pollutants. A two-week experimental campaign was conducted in an apartment in Lyon, France, known for its poor urban air quality, assessing temperature, relative humidity, CO2, and PM2.5 concentrations. A model verification study was performed to compare experimental measurements against numerical modeling in the living room and bedroom, leading to errors in the accuracy of the sensors. In addition, this study also investigates the impact of different ventilation strategies on indoor air quality. This research evaluates a baseline mechanical exhaust-only ventilation approach with constant air volume against two innovative smart ventilation approaches: mechanical exhaust-only ventilation with humidity control and mechanical exhaust-only ventilation with room-level CO2 and humidity control. A key contribution of this research is the novel coupling of multizone simulation models (DOMUS and CONTAM) with a CFD tool to refine pressure coefficients on the building façade, which enhances the accuracy of indoor air quality predictions. The smart ventilation strategies showed improvements, including a 20% reduction in CO2 concentration and a 5% reduction in the third-quartile PM2.5 concentration, highlighting their effectiveness in enhancing ventilation and pollutant dilution. This research provides valuable insights into advanced ventilation strategies and modeling techniques in urban environments.